2001
DOI: 10.1080/00305364.2001.11745252
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three procedures for initial fitting of compression hearing aids. I. Experienced users, fitted bilaterally

Abstract: We compared the effectiveness of three procedures for the initial fitting of hearing aids with multi-band compression: (1) CAMEQ, which aims to amplify speech so as to give equal loudness per critical band over the frequency range important for speech intelligibility, and to give similar overall loudness to 'normal': (2) CAMREST, which aims to amplify speech so as to restore 'normal' specific loudness patterns, over a wide range of speech levels; (3) DSL I/O, which aims to map the dynamic range of normally hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 27 publications
2
19
3
Order By: Relevance
“…This difficulty is only partly alleviated by the use of hearing aids (Moore et al, 2001). Moreover, hearingimpaired listeners achieve less binaural gain in intelligibility than normal-hearing listeners when the speech and background sources are spatially separated (Levitt and Rabiner, 1967;Bronkhorst and Plomp, 1989;Koehnke and Besing, 1997;Richards et al, 2006;Moore et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…This difficulty is only partly alleviated by the use of hearing aids (Moore et al, 2001). Moreover, hearingimpaired listeners achieve less binaural gain in intelligibility than normal-hearing listeners when the speech and background sources are spatially separated (Levitt and Rabiner, 1967;Bronkhorst and Plomp, 1989;Koehnke and Besing, 1997;Richards et al, 2006;Moore et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials that have compared DSL[i/o] with alternative fitting procedures generally have shown that adults prefer less gain than prescribed by DSL, either from a lower-gain prescription such as CAMFIT (Moore et al, 2001) or from a patient-driven procedure that customizes gains to preference (Lindley and Palmer, 1997).…”
Section: Outcomes For Adultsmentioning
confidence: 99%
“…Clinical trials that have compared DSL[i/o] with alternative fitting procedures generally have shown that adults prefer less gain than prescribed by DSL, either from a lower-gain prescription such as CAMFIT (Moore et al, 2001) or from a Between 1999 and 2000, we entered into a clinical collaboration with two audiology clinics that routinely used the DSL Method v4.1 with their adult populations. The audiologists at these clinics were interested in beginning a routine hearing instrument outcome test battery, in part because of the recent attention outcome measurement has received in the literature (e.g., Humes, 1999).…”
Section: Outcomes For Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, since the release of the computer-assisted implementation of DSL v4.1 in 1997, anecdotal reports from clinicians, research studies in our laboratory, and published studies indicated some modifications could be applied to the algorithm for more appropriate adult application (e.g., Moore et al, 2001).…”
Section: Comparisons Among Hearing Instrument Prescriptive Formulasmentioning
confidence: 99%